Identification of topologically characteristics musculoskeletal pain occurence amoung young female atheletes: Musculoskeletal pain in gymnasts - Miletic, A.; Kezic, A.; Delaš Kalinski, S. (Science of Gymnastics Journal, 2023)
The purpose of this study was to identify pain occurrence among young female athletes in aesthetic sports by defining the proportions of pain status of fourteen body regions. Three groups of young female athletes (artistic gymnasts, rhythmic gymnasts and contemporary dancers) were analysed and compared. The sample consisted of overall 99 competitive athletes. Using the "Self-estimated functional inability because of pain" (SEFIP) questionnaire, athletes were asked to assess their current pain status in 14 body regions on a 5-point scale, with 0 being no pain and 4 being pain so severe that they are unable to practice. According to the Wilk`s test there was a significant multivariate effect (F= 4.60; p<0.001) between artistic gymnasts, rhythmic gymnasts and compulsory dancers in training experience and body status. The most common locations for incidence of pain on the total sample of subjects were in the lower back (44%), knees (35%) and ankles/feet (31%). Artistic gymnasts mostly report pain in the ankles/feet (51.43%), and lower (37.14%) and upper back (34.29%). Rhythmic gymnasts of the same age mostly report pain in lower back area (46.42%), knees (42.86%) shins, ankles and feet (28.57%)¸ while dancers experience pain mostly in lower back (50%), upper back (44%) and knees (38.89%). According to the results of the Chi-square test, artistic gymnasts reported significantly higher pain incidence in ankles/feet region (p<0.01). Early detection of even low intensity pain, accompanied with the adjustment of training load and usage of appropriate safety requirements, can prevent the occurrence of injuries among young athletes.